PERAWAT GIGI DALAM PELAKSANAAN PROGRAM UKGS DI PUSKESMAS KABUPATEN BADUNG TAHUN 2015 - I G A Raiyanti; Ni Ketut Ratmini; Ni Nyoman Dewi Supariani (Jurnal Kesehatan Gigi (Dental Health Journal), 2017)
The behavior of dental nurses in the implementation of the program UKGS in Badung;Dental nurses, as the excecutor in the activities of micro-management in dental health care services, especially business school dental health activities of planning, implementation ( promotive, preventive, curative and referral) monitoring and evaluation.The purpose of this study was to determine the factors analysis of the factors that influence the behavior of dental nurse in the implementation of program UKGS in the city of Badung. Explanatory research is research with cross sectional approach.The result showed that 58,6 % of responden behave good  well on the implementation of the program UKGS. Variables related to the behavior of dental nurses in the implementation of the program is the knowledge of the dental nurses UKGS, the attitude of dental nurses, support the head of clinic, the principal support, support dentist and infrastructure.